Minimum wages in Europe: does the diversity of systems lead to a diversity of outcomes? - Kampelmann, Stephan; Garnero, Andrea; Rycx, François (Brussels, 2013)
" Since the mid-2000s, academics, trade unionists and policymakers have been involved in controversial debates about the need for a harmonised European minimum wage policy. This report by three academic experts leaves the beaten track of minimum wage analysis by focussing on the institutional diversity of minimum wage systems within the EU.